DEVELOPING SPEAKING SKILL OF THE EIGHTH GRADE STUDENTS THROUGH SHORT CONVERSATION - Sofyan H; Ferry Rita (e-Journal of ELTS (English Language Teaching Society), 2021)
The objective of the research is to investigate whether or not the application of Short Conversation Technique improve the speaking skill of the eighth grade students of SMPN 1 Palasa. Additionally, this research was conducted through quasi experimental research design in which the samples of the research were grades VIII B and VIII C. The obtained data of this research were analyzed statistically in order to find out the significant difference between two groups on the posttest after the treatment using Short Conversation given to the experimental group. It was found that the mean scores of both the experimental and control groups on the posttest are respectively 75.56 and 61.45. Furthermore, referring to the ttable value of df 46 (24+24-2) by applying 0.05 level of significance on one-tailed test, it is found that the tcounted value of this research (6.1) is higher than the ttable value (1.68). On top of that, the application of Short Conversation Technique can improve the speaking skill of the eighth grade students of SMPN 1 Palasa.